Preconditioning with oil mixes of high ratio Omega-9: Omega-6 and a low ratio Omega-6:Omega-3 in rats subjected to brain ischemia/reperfusion - Pinheiro,Petrúcia Maria Antero (2011)
PURPOSE: This study aimed to assess the effects of preconditioning with mixtures of oils containing high/low ratio of ω-6/ω-3 and ω-9/ω-6, respectively, in an experimental model of cerebral ischemia-reperfusion (I/R). METHODS: Forty-two Wistar rats were randomly distributed into two groups: control (n=24) and test (n=18). Control group was subdivided in 4 subgroups (n=6): G1: Sham-Water; G2: I/R-Water; G3: Sham-Isolipidic and G4: I/R-Isolipid. The animals received water or a isolipid mixture containing ω-3 oils (8:1 ratio) and ω-9/ω-6 (0.4:1 ratio) by gavage for seven days. Test group included 3 subgroups (n=6) G5: I/R-Mix1, G: 6 I/R-Mix2 and G7: I/R-Mix3. Test group animals received oily mixtures of ω-3 (1.4:1 ratio) and ω-6 (3.4:1 ratio), differing only in source of ω-3: G5 (alpha-linolenic acid); G6 (alpha-linolenic, docosahexaenoic and eicosapentaenoic acids), and G7 (alpha-linolenic and docosahexaenoic acids). On day 7 I/R rats underwent cerebral ischemia with bilateral occlusion of common carotid arteries for 1 hour followed by reperfusion for 3 hours. G1 and G3 animals underwent sham operation. Concluded the experiment, animals were decapitated and their brains sliced for red neurons (RN) count in CA3 area of the hippocampus. Variables were compared using ANOVA-Tukey test. RESULTS: The use of different mix preparations promoted a decrease in red cell count in all three groups (G5/G6/G7), compared with G2/G4, confirming the protective effect of different oil blends, regardless of ω-3 source. CONCLUSION: Pre-conditioning with mixtures of oils containing high ratio ω-6/ω-3 and low ω-9/ω-6 relationship protects brain neurons against I/R injury in an experimental model.